Promoting maturation and contractile function of neonatal rat cardiomyocytes by self-powered implantable triboelectric nanogenerator. (1st December 2022) - Zhao, Luming; Gao, Zhongbao; Liu, Wei; Wang, Chunlan; Luo, Dan; Chao, Shengyu; Li, Siwei; Li, Zhou; Wang, Changyong; Zhou, Jin
Abstract: Cardiomyocyte-based therapeutic strategy is a promising approach to treat myocardial injury; however, the prognostic power of this approach is currently limited by the immaturity of cardiomyocytes. Here, a flexible self-powered implantable electrical stimulator based on the triboelectric nanogenerator (TENG) was proposed to induce the maturation of cardiomyocytes by generating an electric field on the interdigitated electrode. The results showed that the TENG-based self-powered stimulator significantly promoted the maturation of neonatal rat cardiomyocytes (NRCMs) in vitro by increasing the expression of connexin 43, α-actinin, and c-troponin T. In addition, electrical stimulation also improved sarcomere organization and fracture formation, and significantly increased the intracellular Ca 2+ levels, Ca 2+ transient rate, and Ca 2+ peak amplitudes of cardiomyocytes. TENG was also shown to be driven by the breath of rats and the heartbeat of rabbits, suggesting it could be used as an implantable medical electronic device for electrically promoting the maturation of neonatal cardiomyocytes. This work develops a TENG-based self-powered implantable medical device, which provides important technical support for clinical treatment of myocardial defects and restoration of the physiological function of cardiac tissue. Graphical Abstract: In this work, a flexible self-powered implantable electrical stimulator based on the triboelectric nanogenerator (TENG) was proposed to induce the maturation of cardiomyocytes by generating an electric field on the interdigitated electrode. The results showed that TENG-based self-powered stimulator significantly promoted the maturation of neonatal rat cardiomyocytes (NRCMs) in vitro by increasing the expression of connexin 43, α-actinin, and c-troponin T. In addition, electrical stimulation also improved sarcomere organization and fracture formation, and significantly increased the intracellular Ca 2+ levels, Ca 2+ transient rate, and Ca 2+ peak amplitudes of cardiomyocytes. TENG was also shown to be driven by the daily breathing of rats and the heartbeat of rabbits, suggesting it could be used as an implantable medical electronic device for electrically promoting the maturation of neonatal cardiomyocytes. This work develops a TENG-based self-powered implantable medical device, which provides important technical support for clinical treatment of myocardial defects and restoration of the physiological function of cardiac tissue. ga1 Highlights: A flexible self-powered electrical stimulator based on TENG was proposed to induce the maturation of cardiomyocytes. Both contractile and electrophysiological performance of cardiomyocytes were enhanced by TENG stimulation obviously. The self-powered electrical stimulator was shown to work with the breath of rats and the heartbeat of rabbits.